Acid sphingomyelinase activity suggests a new antipsychotic pharmaco-treatment strategy for schizophrenia - Chestnykh, Daria; Mühle, Christiane; Schumacher, Fabian; Kalinichenko, Liubov S.; Löber, Stefan; Gmeiner, Peter; Alzheimer, Christian; von Hörsten, Stephan; Kleuser, Burkhard; Uebe, Steffen; Ekici, Arif Bülent; Gulbins, Erich; et al. (Molecular psychiatry, 2025)
Schizophrenia is a chronic and severe mental disorder. It is currently treated with antipsychotic drugs (APD). However, APD’s work only in a limited number of patients and may have cognition impairing side effects. A growing body of evidence points out the potential involvement of abnormal sphingolipid metabolism in the pathophysiology of schizophrenia. Here, an analysis of human gene polymorphisms and brain gene expression in schizophrenia patients identified an association of SMPD1 and SMPD3 genes coding for acid- (ASM) and neutral sphingomyelinase-2 (NSM). In a rat model of psychosis using amphetamine hypersensitization, we found a locally restricted increase of ASM activity in the prefrontal cortex (PFC). Short-term haloperidol (HAL) treatment reversed behavioral symptoms and the ASM activity. A sphingolipidomic analysis confirmed an altered ceramide metabolism in the PFC during psychosis. Targeting enhanced ASM activity in a psychotic-like state with the ASM inhibitor KARI201 reversed psychotic like behavior and associated changes in the sphingolipidome. While effective HAL treatment led to locomotor decline and cognitive impairments, KARI201 did not. An RNA sequencing analysis of the PFC suggested a dysregulation of numerous schizophrenia related genes including Olig1, Fgfr1, Gpr17, Gna12, Abca2, Sox1, Dpm2, and Rab2a in the rat model of psychosis. HAL and KARI201 antipsychotic effects were associated with targeting expression of other schizophrenia associated genes like Col6a3, Slc22a8, and Bmal1, or Nr2f6a, respectively, but none affecting expression of sphingolipid regulating genes. Our data provide new insight into a potentially pathogenic mechanism of schizophrenia and suggest a new pharmaco-treatment strategy with reduced side effects.
Gesehen am 25.07.2025